A study of knowledge attitude practices and identification of perceived barriers towards screening for diabetic retinopathy amongst diabetics in an industrial area in western Maharashtra - Bakare, Prachi; Sethi, Sejal; Mushtaq, Iqra; Maheshgauri, Rupali; Magdum, Renu; Modani, Neha Kamalkishor; Gogate, Parikshit (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Diabetic retinopathy (DR) screening is first step in prevention of diabetic retinopathy related ocular morbidity. The aim of the study was to assess the gaps in the knowledge and awareness and evaluate its effects on the attitude and practice in known diabetic patients and to assess any anticipated barriers and its association with knowledge, attitude and practices. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A closed-ended questionnaire was given to 112 diabetics who met the inclusion criteria and visited a tertiary eye hospital in western Maharashtra. The purpose of the questionnaire was to assess knowledge, attitude and practices and perceived barriers to the study of DR. The statistical analysis was done on SPSS software. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In our study, 73.4% did not know about DR, suggesting poor awareness about the disease, 59.5% did not feel the need for regular eye checkup. 67 (61.1%) had no knowledge about blood sugar control level and lipid control for effective control of DR, 89 (79.5%) of participants did not know about effective treatment options. Moreover, 74 (66.1%) participants were advised for DR screening by physician, while 60 (53.5%) were willing to get screened, negative attitude was not getting screened when vision is good seen in 87 (79.1%) participants. Furthermore, 84 (75%) patient think eye checkup are expensive, 66% people believe availability of doctor is an issue. 60 (54.5%) think that eye checkups are time consuming. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Our study demonstrated, that Spearman’s correlation coefficient between knowledge and awareness and based on attitude and practice, is 0.54, and that this is statistically significant (p<0.01). Our study has shown poor awareness and knowledge about the disease thus affecting attitude and practices, eye screening is considered expensive has been pointed out a major barrier in this study.